2006
DOI: 10.1111/j.1740-0929.2006.00383.x
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of vancomycin‐resistant enterococci transmission from human to broilers, and possibility of using the vancomycin‐resistant gram‐positive cocci as a model in a screening study of vancomycin‐resistant enterococci infection in the broiler chick

Abstract: In this study, vancomycin‐resistant enterococci (VRE) from humans and vancomycin‐resistant gram‐positive cocci (VRPC) from pigs were examined for their ability to transmit in the chick intestine (Experiment 1). A model study on the spread speed of VRPC was also estimated from chick to chick under semi‐production conditions with different administration routes (not inoculated, oral administration to a chick, sprayed on the floor) (Experiment 2). Furthermore, the disappearance of VRPC from their litter with comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…Backyard chickens possibly acquired the CC17 E. faecium isolates from contaminated environments, or humans visiting the farm. This suggestion is supported by a previous study that demonstrated the transmission of E. faecium of human origin to chickens [96]. Moreover, human-linked E. faecium has been isolated from various water and food sources [97,98].…”
Section: Discussionsupporting
confidence: 69%
“…Backyard chickens possibly acquired the CC17 E. faecium isolates from contaminated environments, or humans visiting the farm. This suggestion is supported by a previous study that demonstrated the transmission of E. faecium of human origin to chickens [96]. Moreover, human-linked E. faecium has been isolated from various water and food sources [97,98].…”
Section: Discussionsupporting
confidence: 69%
“…We believe that it is possible that the chicken acquired the ST203 E. faecium strain from contaminated environments, other animals, or humans working on or visiting the farm. Our assertion is supported by an experimental study that demonstrated transmissibility of VRE of human origin to broiler chickens (47). Furthermore, human-adapted VRE strains have been recovered from various food and urban water sources (43,(48)(49)(50).…”
Section: Discussionsupporting
confidence: 63%
“…Chickens can possibly acquire the CC17 E. faecium isolates from contaminated environments or humans visiting the farm. This idea is reinforced by a study that showed the transmission of E. faecium of human origin to chickens [ 251 ]. E. faecium ST492 isolates found in broilers were clustered with the human isolates, which may also indicate reverse zoonotic transmission from humans to chickens along the production chain [ 60 ].…”
Section: Impact Of Antibiotic Usage and Antibiotic-resistant Bacteria...mentioning
confidence: 99%